A pulse radiolysis study of hyperoside isolated from Hypericum mysorense. (February 2015) - Hariharapura, Raghu C.; Mahal, H.S.; Srinivasan, R.; Jagani, Hitesh; Vijayan, P.
Abstract: Background: The recent growth in knowledge of free radicals in biology is producing a medical revolution that promises a new age in health and disease management. In the last two decades there has been an explosive interest in the role of oxygen free radicals, more generally known as "reactive oxygen species" and of "reactive nitrogen species" in experimental and clinical medicine. Methods: The flowering top extract of Hypericum mysorense possessing potent anti-oxidant activity was subjected to bio-active guided isolation. Pulse radiolysis technique was used to determine the transient spectrum and rate constant for the one-electron oxidation of hyperoside by O H, N 3, NO 2, NO, CCl 3 OO radicals in aqueous solution. Results: Three compounds were isolated and characterized as rutin, quercetin-3- O -galactoside (hyperoside) and quercetin from spectral analysis. The hyperoside radical showed pKa1 and pKa2 at 5.4 and 9.2. Both, Cu(II) and iron(II) ions form chelate with hyperoside. The Cu–hyperoside chelate was able to scavenge O 2 −, k= 7.0(±0.3)×10 6  dm 3  mol −1  s −1 at pH 9. The repair rates for tryptophan and guanosine radicals by hyperoside were also determined. Conclusion: The reduction potential of hyperoside radical was determined by cyclic voltammetric and pulse radiolysis methods. Highlights: Hyperoside, rutin and quercetin were isolated from extract of Hypericum mysorense . Rate constant of hyperoside was determined by Pulse radiolysis technique. The hyperoside radical showed pKa1 and pKa2 at 5.4 and 9.2. Cu(II) and iron(II)ions form chelate with hyperoside. Hyperoside can repair the damage to guanosine, tryptophan radicals.